Mejora en el proceso de autenticación utilizando la metodología Six Sigma en la empresa Alignet S.A.C. - Correa Cardenas, Christian Jefferson (2020)
The purpose of this project is to increase the authentication percentage for the virtual purchasing process using digital payment methods by using the Six Sigma methodology in the company Alignet S.A.C. This is how migration to protocol 2.0 has been proposed as a possible solution, where the mobile channel is used for cardholder authentication with the help of biometrics. The result of this implementation is to be able to capture a greater number of transactions in e-commerce and in turn be authenticated more efficiently, safely and quickly in order to reduce fraud, thus achieving a percentage of 79% as a result. DMAIC tools will be used which has the following steps: Define, Measure, Analyze, Improve, and Control. These are intended to guide the project and generate an added value to the research.Within the Define phase, it details the current situation of the company, its processes, the formation of the team in charge of the project and the needs of the client. For the Measure phase, the behavior and capacity of the authentication process is contemplated and the main indicator, the efficiency in the authentication platform. The Analyze phase, part of identifying opportunities for improvement and the causes of low authentication percentage (46%) so that we can prioritize possible solutions. Then, in the Improve phase we can find the deployment of the solution previously evaluated in conjunction with the company, based on mobile channel transaction authentication via biometrics. Finally, for the Control phase, a hypothesis analysis was performed in Excel to validate the improvement proposal and demonstrate the feasibility of the project and its impact.